Innate and adaptive immune responses in chronic hepatitis B virus infections: towards restoration of immune control of viral infection. Issue 12 (9th December 2011) - Bertoletti, Antonio; Ferrari, Carlo
Abstract : Knowledge of the immunological events necessary to control hepatitis B virus (HBV) infection has accelerated in recent years, but their translation towards therapeutic strategies able to achieve a durable HBV suppression has been challenging. The scenario of how HBV deals with the host immunity is presented and used to discuss how the immune response can be harnessed to potentially achieve infection control.